Family & other calamities : a novel - Streeter, Leslie Gray (Lake Union Publishing, 2025)
"Entertainment journalist Dawn Roberts has a lot to work through: a widow's grief, betrayals of family and friends, and scandals that almost tanked her reputation. Not that Dawn dwells on the past. Well, hardly. When she returns to Baltimore with her husband's ashes, she can't avoid it. In fact, she's diving into decades of backstabbing and treachery for her first trip home in years. She's looking at you, Joe Perkins. Her former mentor, whose explosive exposé about big-city corruption is being turned into a slanderous movie, is also back in town. The villain of the piece? Dawn. The good news is that this could all be a chance to reset-heal family wounds, admit to her own mistakes, and maybe even reconnect with the one who got away. Oh, and get even with Joe any way she can. With the surprising help of an up-and-coming journalist and a legendary R & B diva, Dawn will finally set the record straight. Returning home might just be the biggest story in Dawn's life, a fresh start-and happy ending-she never expected." -- Publisher annotation.